A faux hawk fullerene with PCBM-like properties1. Issue 3 (16th March 2015) - San, Long K.; Bukovsky, Eric V.; Larson, Bryon W.; Whitaker, James B.; Deng, S. H. M.; Kopidakis, Nikos; Rumbles, Garry; Popov, Alexey A.; Chen, Yu-Sheng; Wang, Xue-Bin; Boltalina, Olga V.; Strauss, Steven H.
<x xml:space="preserve">Abstract</x> A fluorinated faux hawk fullerene with comparable OPV-relevant TRMC performance and far greater thermal stability than PCBM is reported.